1993
DOI: 10.1016/0014-5793(93)80060-8
|View full text |Cite
|
Sign up to set email alerts
|

On the production of α,β‐heterodimeric acyl‐coenzyme A: isopenicillin N‐acyltransferase of Penicillium chrysogenum

Abstract: A high level E coli expression system has been constructed for the Penicillium chrq'sogenum penDE gene, which encodes the acyl-coenzyme A: isopenicilhn N-acyltransferase (AT) enzyme. Induction of overexpression of recombinant AT (recAT) by increasing the growth temperature of the host adversely affected solubility and activity of the AT enzyme. Addition of isopropylthio-/?-o-galactopyranoside (IPTG) at decreased growth temperatures (less than 32°C) resulted in the overproduction of soluble. active recAT. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Self-processing is known to occur in the penicillin-biosynthetic enzyme isopenicillin N : phenylacetyl-CoA acyltransferase ( [25] and Ferna! ndez, F. J., Montenegro, E., Velasco, J., Gutie!…”
Section: Discussionmentioning
confidence: 99%
“…Self-processing is known to occur in the penicillin-biosynthetic enzyme isopenicillin N : phenylacetyl-CoA acyltransferase ( [25] and Ferna! ndez, F. J., Montenegro, E., Velasco, J., Gutie!…”
Section: Discussionmentioning
confidence: 99%
“…For soluble expression of the full-length Xenopus IRBP an even lower temperature (25mC) is required . In a variety of expression systems soluble expression is enhanced by lower induction temperatures (Craig and Kumar, 1996 ;Yasueda et al, 1995 ;Mak, Loh and Yap, 1993 ;Aplin et al, 1993). However, this is not true for all expression systems (Sitney et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The great specificity of the antibodies, as shown by the lack of immunoreaction with extracts of the deletion mutant npelO, strongly supports the conclusions that all mutants are able to form the 40-kDa IAT and that all of them are able to process the 40-kDa polypeptide into the 29-kDa subunit. The processing of the 40-kDa IAT into the 29-and 11-kDa subunits is now well established (3,6,28). Tobin and coworkers (28) proposed that the IAT is processed autocatalytically into its subunits.…”
Section: Xhoi Xmni Hincii Hinclimentioning
confidence: 99%
“…The last step involves the exchange of the aL-aminoadipic acid side chain of isopenicillin N (IPN) by phenylacetic acid (activated as phenylacetylcoenzyme A [CoA] or phenylacetylglutathione) (2); this reaction is catalyzed by the enzyme acyl CoA:isopenicillin Nacyltransferase (IAT), encoded by the penDE gene, an enzyme that shows four other related activities (2). The IAT is a heterodimer (3,28,32) formed of two subunits of 29 and 11 kDa which are encoded by a single gene, penDE, both in Penicillium chrysogenum (6,29) and inAspergillus nidulans (21,29). Initial studies indicated that a single transcript of 1.15 kb encoding both subunits was formed, and a 40-kDa form of the IAT was observed in addition to the 29-and 11-kDa subunits, suggesting that a 40-kDa precursor protein is posttranslationally cleaved to form the two subunits (6,32).…”
mentioning
confidence: 99%